Graphene-based tunable Bragg reflector with a broad bandwidth - Tao, Jin (2018)
We show theoretically that Bragg stopband and defect resonance mode can be achieved and dynamically tuned over a wide wavelength range by a small change in Fermi energy level of graphene, in graphene plasmonic waveguide structures.